Medicalitation of education (Journal of Parents and Teachers, 2013)
The number of students, who receive pharmacological treatment to intellectual and emotional difficulties detected in the classroom, has increased significantly in recent years. There are reasons to believe that this increase may not respond exclusively to medical factors. This article discusses some social attitudes that could increase this phenomenon and identifies some reasons for its widespread implantation, its consequences and the most important challenges in order to change this inertia.
Keywords: The number of students; who receive pharmacological treatment to intellectual and emotional difficulties detected in the classroom; has increased significantly in recent years. There are reasons to believe that this increase may not respond exclusively